Quantifying the effects of competition on the dimensions of Scots pine and Norway spruce crowns - Pitkänen, T.P.; Bianchi, S.; Kangas, A. (Elsevier BV, 2022)
Inter-tree competition can be assessed using relatively simple indices derived from tree diameters, heights and locations, but they have often been found to be deficient for predicting tree growth. To better understand these linkages, we measure dimensions of Scots pine and Norway spruce crowns, which are assumed to be affected by competition pressure. We extract these features from terrestrial laser scanning point clouds and model their dependencies on competition. Our results indicate that while competition is a major determinant for crown morphology, the characteristics and most applicable indices of the two species are contrasting. We interpret our results primarily by light competition: pines are seeking for light and invest their resources on widening the crown only in suitable conditions, while spruce may grow large despite of shortage of light. We conclude that shade tolerance affects strongly on the identification of actual competitors, which should be addressed when modelling competition.
Keywords: tree crown; Competition indices; Terrestrial laser scanning; Tree growth modelling